1972
DOI: 10.1017/s0022172400022403
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the antigens present on the surface of virus released artificially from chick cells infected with vaccinia virus, and cowpox virus and its white pock mutant

Abstract: SUMMARYAntisera prepared against vaccinia and cowpox viruses were absorbed with purified suspensions of vaccinia virus, red cowpox and white cowpox viruses. They were then tested for their ability to neutralize the viruses, and to precipitate the virus soluble antigens.The results showed that some virus specific antigens were not virus surface components and that some components were present on the surface of all three viruses. However, certain components were detected on the surface of vaccinia virus but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The ihndamental significance of the vaccinia envelope in the biology a, nd pathogenesis of vaccinia requires that an investigation be made of human pathogenic poxviruses for the existence of an enveloped form. Cowpox is very closely related antigenically to vaccinia (1,5). The present report presents evidence for the occurrence of an enveloped form of cowpox and that the envelope contains antigens related to those in the envelope of vaccinia.…”
Section: Introductionsupporting
confidence: 51%
“…The ihndamental significance of the vaccinia envelope in the biology a, nd pathogenesis of vaccinia requires that an investigation be made of human pathogenic poxviruses for the existence of an enveloped form. Cowpox is very closely related antigenically to vaccinia (1,5). The present report presents evidence for the occurrence of an enveloped form of cowpox and that the envelope contains antigens related to those in the envelope of vaccinia.…”
Section: Introductionsupporting
confidence: 51%
“…The results obtained may be due to qualitative differences in the heat stable surface antigens of the viruses, as has already been demonstrated for vaeeinia and cowpox viruses (1). Alternatively the results may be due to differences in the amount or importance of shared surface antigens.…”
Section: Table 1 Neutralization Titres Of Antise~um To Heat-inactivamentioning
confidence: 81%
“…During a detailed comparison of the surface antigens of vaccinia and cowpox viruses the chance observation was made that antisera made against heat-inactivated vaccinia virus would neutralize that virus but not cowpox virus (1). This result suggested that the genus Orthopoxvirus might be sub-divided on the basis of this simple test, and this paper describes the results obtained.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…For reasons still not clearly understood, vaccinia virus is often a more sensitive indicator of cowpox neutralizing antibody than cowpox itself (Baxby, 1972). All the sera were therefore initially tested for neutralizing antibody by using vaccinia virus.…”
Section: Virus Neutralization Tests (Vn)mentioning
confidence: 99%